The Three Angelsâ€™ Messages in the Challenging Times - Glenn Jade Mariano (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2023)
The three angelsâ€™ messages (3AM) in Rev 14:6â€“13 are worldwide in scope. They contextually fit in the COVID-19 pandemic and other challenging situations. The message, media, and mission of the Seventh-day Adventist Church are embedded in the 3AM. The identity of the target addressees, proclaiming angels, timing, and meaning of the 3AM are investigated in connection to the message, media, and mission of the church through the lens of the biblical-historical method of exegesis and historicism. The proclamation of the 3AM to the target fivefold group (â€œthe earth-dwellersâ€ and â€œevery nation, tribe, tongue, and peopleâ€) is significantly relevant to the current pandemic and troublous times in preparation for the impending punitive judgment and the second coming of Jesus Christ.